Body composition of New Zealand-born term babies differs by ethnicity, gestational age and sex. (January 2020) - Alexander, T.; Conlon, C.A.; Gamble, G.; von Hurst, P.R.; van Dorp, L.; Ichhpuniani, B.; Housh, R.; Ke, P.; Bloomfield, F.H.
Abstract: Background: Body composition provides important information on nutrition and future metabolic risk. New Zealand has a diverse ethnic population for which there are no newborn body composition data. Aim: To determine body composition in a cohort of New Zealand-born term babies. Study design: Observational study. Subjects: Healthy, term infants between 37 +0 and 41 +6 weeks' gestation in two hospitals in Auckland, New Zealand. Outcome measures: Body composition by air displacement plethysmography and anthropometry measured within 5 days of birth. Parent-identified ethnicity was prioritised according to Ministry of Health criteria. Data were analysed using t -test, ANOVA with Tukey post-hoc tests, quantile regression and are mean(SD). Results: 440 babies (54% male) were included. Pacific Island/Māori (PI/M) were heavier at birth than Asian/Middle Eastern/Latin American/African (Asian+) babies (3403(506) vs 3181(485) g, p  < .05). PI/M and European (E) babies were longer with larger head and waist circumferences than Asian+ babies (all p < .05). Absolute fat mass (FM) was not different amongst ethnicities (E, 365(156), PI/M, 347(183), Asian+, 357(188) g) but PI/M babies had significantly lower FM% than Asian+ (9.8(4.3) vs 10.9(4.5) %, p  < .05). Fat-free mass (FFM) was greater in PI/M (3056(400) g) than E (2952(345) g ( p  < .05) and both PI/M and E had greater FFM than Asian+ (2824(363) g, p < .05). Early term babies had less FFM than term and late-term babies (2732(370), 3012(352), 3173(302)g, p  < .001) respectively. Conclusions: Asian+ babies were the smallest babies with the least FFM yet had similar FM and the highest FM%, indicative of a thin, fat phenotype from birth. Highlights: Absolute fat mass was similar across ethnicities. Asian+ babies had the highest % fat mass and the lowest fat-free mass, consistent with a thin-fat phenotype. Pacific Island and Māori babies have more fat-free mass. Increasing gestational age results in higher birth weight primarily due to increased fat-free mass.